Issues of air pollution in environmental impact assessment of development projects - Nor Azam Ramli; Wathern , Peter; Muhammad Rizal Razman (Environmental Management Society, Malaysia, 2003)
The aim of this study is to establish the trends in approaches and techniques being used to address the air pollution issues in project-related development. The interest was to look at the overall issues of air pollution and how it was dealt with in the context of Environmental Impact Assessment (EIA). However, the review was not based upon individual Environmental Impact Assessment techniques. Twenty eight samples from four different sectors were reviewed and information pertaining to construction activities, baseline condition, impact predictions and mitigating measures were extracted and analyzed. It was established that only 17% of reports had described the existing air quality in an appropriate manner. The constructions activity was mainly confused with the description of intended development. Only 39 % had described the activities as ‘true’ construction activities. The impacts of the construction phase on air quality for all projects were mainly associated with the generation of dust and particulates and emissions from vehicles exhaust. The predictions were made through quantitative or qualitative techniques. The later were being used in most projects. Nevertheless, there are reports especially from road schemes, which did not mention, the impacts of construction phase of the projects on air quality, at all. There are common mitigating measures to all or most projects types such as; wetting of exposed earth surfaces and unpaved roads, covering transported materials which may potentially release dust and particles, imposing speed limits within construction site. In order, to ensure that the mitigation measures will be implemented, the written approval should be linked with terms and conditions, which include the implementation of all mitigation measures identified